Effects and Side Effects of Platelet Transfusion - Cognasse, Fabrice; Hally, Kathryn; Fauteux-Daniel, Sebastien; Eyraud, Marie-Ange; Arthaud, Charles-Antoine; Fagan, Jocelyne; Mismetti, Patrick; Hamzeh-Cognasse, Hind; Laradi, Sandrine; Garraud, Olivier; Larsen, Peter (Hämostaseologie, 2021)
Aside from their canonical role in hemostasis, it is increasingly recognized that platelets have inflammatory functions and can regulate both adaptive and innate immune responses. The main topic this review aims to cover is the proinflammatory effects and side effects of platelet transfusion. Platelets prepared for transfusion are subject to stress injury upon collection, preparation, and storage. With these types of stress, they undergo morphologic, metabolic, and functional modulations which are likely to induce platelet activation and the release of biological response modifiers (BRMs). As a consequence, platelet concentrates (PCs) accumulate BRMs during processing and storage, and these BRMs are ultimately transfused alongside platelets. It has been shown that BRMs present in PCs can induce immune responses and posttransfusion reactions in the transfusion recipient. Several recent reports within the transfusion literature have investigated the concept of platelets as immune cells. Nevertheless, current and future investigations will face the challenge of encompassing the immunological role of platelets in the scope of transfusion.
Keywords: platelet physiology; transfusion medicine; inflammatory mediators